Experience in the development of assessment tools validation of formation of professional competences of graduates of pedagogical universities - Ekaterina G. Gureeva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки, 2018)
Modern pedagogy actively discusses the issue of assessing the educational results of higher education, both General cultural and General professional competences and professional competences of graduates. Russian and foreign authors justify and offer professional models of graduates, design of systems of professional competences in various areas of training of bachelors. The focus of the teachers are two aspects - the formulation of educational results and their evaluation. At the same time there is a problem of assessment of competences as readiness of the graduate to professional activity, instead of the sum of the resource results necessary for formation of competence or understanding of the activity. For future teachers, the formation of competence-based educational results and tools for their evaluation is necessary in the context of the implementation of the requirements of state educational standards at all levels, as well as the requirements of professional standards in secondary vocational and higher education.The article discusses the possibility of assessing the professional competencies of graduates of pedagogical universities, characterized by groups of educational results, emphasizes that the competence-based educational results necessarily include formed experience, defined requirements for the formulation of educational results, provides an algorithm for assessing educational results, on the example of the direction of training «Teacher education» demonstrates the model of professional competence and ways of its evaluation.The proposed list of competence-based educational results can be used in the training of future teachers, and the algorithm for evaluating educational results adapted for other areas of higher education.The results of testing of the evaluation tool showed the readiness of graduates for teaching professional activities, transparency of the evaluation procedure and improving the quality of training of future teachers.